Charakterisierung und Bewertung der Zug- und Ermüdungseigenschaften von Mikrobauteilen aus 17-4PH Edelstahl - Ein Vergleich von mikropulverspritzgegossenem und konventionell hergestelltem Material - Slaby, Stefan Andreas (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
This book investigates the tension, fatigue and microstructural properties of micro powder injection molded (µPIM) 17-4PH stainless steel components typically used in micro systems technology. The comparison with conventional produced bulk material showed already comparable mechanical properties but need for microstructural optimization.